2015
DOI: 10.1002/cnma.201500018
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid‐Dependent Host–Guest Interaction: Polyglycerol Dendrimer of Generation 3 Encapsulates Amino Acids Bearing Two Amino Groups

Abstract: Ap olyglycerol dendrimer (PGD), which is known as ab iocompatible compound,w as demonstrated as ah ost molecule for aminoa cids. PGD of generation 3( PGD-G3) was found to interactw ith basic a-aminoa cids such as l-arginine (Arg) and l-lysine (Lys) in water.The resultsofi sothermal titration calorimetry, 1 HNMR, and 1 H-1 HN OESY NMR measurements revealed that two basic groups in a-amino acids were essential for encapsulationb yP GD-G3. An increase in the pK a value of the amino acid side chains (Arg > Lys > H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Unlike HPGs, PGDs exhibit well‐defined nanostructures with narrow molecular weight distributions, resulting in higher reactivity and loading efficiency compared to other molecules . In our previous study, we found that a generation 3 PGD (PGD‐G3) specifically interacted with amino groups of l ‐arginine in aqueous solution . Therefore, one can imagine that the amino group of chitosan may interact with PGDs, enabling us to form a PGD‐based hydrogel.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike HPGs, PGDs exhibit well‐defined nanostructures with narrow molecular weight distributions, resulting in higher reactivity and loading efficiency compared to other molecules . In our previous study, we found that a generation 3 PGD (PGD‐G3) specifically interacted with amino groups of l ‐arginine in aqueous solution . Therefore, one can imagine that the amino group of chitosan may interact with PGDs, enabling us to form a PGD‐based hydrogel.…”
Section: Figurementioning
confidence: 99%
“…A 1 H NMR spectrum of the PGD‐G3/GC hydrogel (Figure S4 c) shows that the peak attributed to the proton next to an amino group of GC, H a ( δ =2.54 ppm, Figure S4 b), was split and shifted to H a“ and H a‘ ( δ =2.59 and 2.74 ppm). The observed peak splitting to H a“ and H a‘ indicates an interaction between PGD‐G3 and GC similar to that described in a previous report: PGD‐G3 formed a complex with basic amino acids in aqueous media . To confirm the amino group recognition, we mixed PGD‐G3 with different types of polysaccharides without amino groups (dextran (Dex), carboxymethyl cellulose (CMC), and hyaluronic acid (HA): Figure S5).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…1) are dendrimers comprising glycerol units, which along with hyperbranched polyglycerols (HPGs) have been extensively studied for biomedical applications [19,20,21,22,23,24,25,26,27]. Unlike HPGs, PGDs are branched molecules with defined molecular weights [28] and thus support host-guest interactions in a stoichiometric manner [29,30,31,32]. We have focused on PGDs as biomaterials rather than HPGs because of their perfect dendrimer characteristics: the degree of branching (DB) of PGDs is 100%, whereas that of HPGs is 50-60% [19].…”
Section: Introductionmentioning
confidence: 99%